Future of the Renal Biopsy: Time to Change the Conventional Modality Using Nanotechnology. (19th February 2017) - Khosroshahi, Hamid Tayebi; Abedi, Behzad; Daneshvar, Sabalan; Sarbaz, Yashar; Shakeri Bavil, Abolhassan
Abstract : At the present time, imaging guided renal biopsy is used to provide diagnoses in most types of primary and secondary renal diseases. It has been claimed that renal biopsy can provide a link between diagnosis of renal disease and its pathological conditions. However, sometimes there is a considerable mismatch between patient renal outcome and pathological findings in renal biopsy. This is the time to address some new diagnostic methods to resolve the insufficiency of conventional percutaneous guided renal biopsy. Nanotechnology is still in its infancy in renal imaging; however, it seems that it is the next step in renal biopsy, providing solutions to the limitations of conventional modalities.